2018
DOI: 10.11648/j.js.20180604.16
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of α-Glutathione S-transferase in Acute Mesenteric Ischemia

Abstract: Background: Acute mesenteric ischemia (AMI) is a life-threatening problem, and the early clinical manifestations of it are non-specific. Despite the advances in laboratory & radiological diagnostic procedures, the mortality rate of AMI is still high. Aim: The purpose of the study to evaluate the ability of α-glutathione S-transferase (α-GST) to predict AMI in patients with abdominal pain. Methods: This prospective study was conducted in Tanta University Hospitals between November 2014 and December 2017. Nighty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In addition to citrulline, alpha-GST is another important constituent of enterocytes. Physiologically, it is involved in cell detoxification, but high plasma levels of alpha-GST indicate intestinal injury and ischemia [56]. While single biomarkers have clinical utility, there are currently studies investigating the power of biomarker panels, where several biomarkers are being determined at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to citrulline, alpha-GST is another important constituent of enterocytes. Physiologically, it is involved in cell detoxification, but high plasma levels of alpha-GST indicate intestinal injury and ischemia [56]. While single biomarkers have clinical utility, there are currently studies investigating the power of biomarker panels, where several biomarkers are being determined at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…In a study including 26 patients with acute abdominal pain, 12 of whom had AMI, plasma alpha-GST was found to be significantly increased in patients with AMI [55]. Moreover, in a prospective study conducted by Elshoura et al, 90 patients were included after clinical suspicion of AMI, confirmed by CT angiography or laparotomy [56]. Patients with intestinal ischemia (n = 52) had significantly higher serum values of alpha-GST, with this marker diagnosing AMI with an accuracy of 84.4% [56].…”
Section: Alpha Glutathione S-transferasementioning
confidence: 99%
See 1 more Smart Citation